Negative outcomes of Internet use: A qualitative analysis in the homes of families with different educational backgrounds - Scheerder, Anique J.; van Deursen, Alexander J. A. M.; van Dijk, Jan A. G. M. (The Information society, 2019)
This study employs a qualitative approach to examine whether and why some societal groups are disadvantaged more by their Internet use than others do. Due to the quantitative nature of most digital divide studies, thorough explanations for why different outcomes exist are lacking. Interviews were conducted with 48 Dutch families selected on the basis of educational level (high or low) and household characteristics (children and marital status). A distinction was made between the types of negative outcomes that families are confronted with and how they cope with those outcomes. The results show that the confrontation with negative outcomes of Internet use in itself seems similar for both educational groups. However, the way Internet users cope with negative outcomes differs between the two educational groups. Members of highly educated groups mostly try to take control themselves when faced with a negative outcome, while members of less educated groups often just experience negative outcomes and do not remedial actions.